Conclusion on the peer review of the pesticide risk assessment of the active substance Bacillus amyloliquefaciens subsp. plantarum strain D747. (4th April 2014) - ,
Abstract: The conclusions of the European Food Safety Authority (EFSA) following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State Germany, for the pesticide active substance Bacillus amyloliquefaciens subsp. plantarum strain D747 are reported. The context of the peer review was that required by Commission Regulation (EU) No 188/2011. The conclusions were reached on the basis of the evaluation of the representative uses of Bacillus amyloliquefaciens subsp. plantarum strain D747 as a fungicide on table and wine grapes. The reliable endpoints concluded as being appropriate for use in regulatory risk assessment, derived from the available studies and literature in the dossier peer reviewed, are presented. Missing information identified as being required by the regulatory framework is listed. The assessment of potential transfer of genetic material from Bacillus amyloliquefaciens subsp. plantarum strain D747 to other organisms cannot not be finalised. The consumer and re‐entry worker risk assessment cannot be finalised as data are missing on the levels of secondary metabolites/toxins produced by the organism on plants. Furthermore, the risk assessment for non‐target organisms and the groundwater exposure assessment from secondary metabolites/toxins could not be finalised. As the soil exposure assessments could not be finalised, also the risk to soil‐dwelling organisms from Bacillus amyloliquefaciens subsp. plantarum strain D747 could not be finalised.